1999
DOI: 10.1017/s0022029999003581
|View full text |Cite
|
Sign up to set email alerts
|

Bovine immunoglobulin G, β-lactoglobulin, α-lactalbumin and serum albumin in colostrum and milk during the early post partum period

Abstract: Colostrum and milk samples from 60 Holstein–Friesian cows were analysed for concentrations and yields of immunoglobulin G (IgG), β-lactoglobulin (β-lg), α-lactalbumin (α-la) and serum albumin (BSA) throughout the first 16 milkings post partum (8 d of lactation) using a single radial immunodiffusion assay. Concentrations (mg/ml, means±SD) at first milking were IgG 59·8±28·5, β-lg 14·3±4·6, α-la 2·04±0·6, BSA 1·21±0·44. Large variations were recorded for IgG concentrations (15·3–176·2 mg/ml) and yields (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
63
0
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 0 publications
19
63
0
16
Order By: Relevance
“…The changes in total protein concentrations reported in this study are also in good agreement with those reported by Božanić [5], Blum and Hammon [4] and Levieux and Ollier [12]. As noted by Gauthier et al [8], the marked decrease in total protein concentration during the first four days of lactation is generally not taken into account in published growth factor concentration data.…”
Section: Discussionsupporting
confidence: 80%
“…The changes in total protein concentrations reported in this study are also in good agreement with those reported by Božanić [5], Blum and Hammon [4] and Levieux and Ollier [12]. As noted by Gauthier et al [8], the marked decrease in total protein concentration during the first four days of lactation is generally not taken into account in published growth factor concentration data.…”
Section: Discussionsupporting
confidence: 80%
“…Colostrum contains elevated levels of IgG, IgA and IgM (Smolenski et al 2007), and immunoglobulins make up 70-80% of the total protein in colostrum (Larson 1992), which is of particular importance to the neonate, as transfer of passive immunity to the calf occurs through colostrum and not via the placenta . Changes in the level and relative proportions of the immunoglobulins in colostrum compared with milk have been reported by several authors (Quigley et al 1994;Levieux and Ollier 1999;Korohnen et al 2000;Elfstrand et al 2002;Zhao et al 2010). The concentration of immunoglobulins in the first milk post-partum can vary considerably, from 30 to 200 mg.mL −1 (Larson 1992;Korohnen et al 1995;Gapper et al 2007).…”
Section: Proteinmentioning
confidence: 95%
“…immediately after parturition (Levieux and Ollier 1999;Nakamura et al 2003;Godhia and Patel 2013), 2 days (Playford et al 2000;Playford 2001), 3 to 4 days (Foley and Otterby 1978;Gopal and Gill 2000;Davis et al 2007;Zhang et al 2011) or 5 to 7 days post-partum (Marnila and Korohnen 2002;Georgiev 2008;Zarcula et al 2010;Abd ElFattah et al 2012). For the purposes of this review, colostrum, unless otherwise defined, will refer to the early milkings from dairy cows, taken up to 3 days post-partum.…”
Section: Introductionmentioning
confidence: 99%
“…Colostral IgG1 concentration was determined via a semi-automated single radial immunodiffusion technique (Mancini et al, 1965;Levieux and Ollier, 1999) using commercial kits (ID Ring BOV IgG; ID Biotech, Issoire, France). Sample dilution was adjusted to meet the manufacturer's recommendations (1000 times).…”
Section: Methodsmentioning
confidence: 99%